Reawakening the Curious Muses: Research, Curatorship, Collections, and Publics at Copenhagen's Medical Museion. Issue 1 (1st July 2021) - Arnold, Ken; Söderqvist, Thomas
Abstract : This conversation between the founding and current directors of the multi-award-winning Medical Museion at the University of Copenhagen was held online, COVID-19-style, in the spring of 2021. We have different backgrounds and instincts. One of us is an academic historian of science, who almost accidentally ended up also running a museum. The other has spent decades working in museums, and then found himself hired as a university professor. Here we discuss the evolution of Medical Museion over the last two decades—the Museion concept, the integration of research and curatorship, the interaction of art and science, the balance between historical contextualization and aesthetic "presence, " the Faustian pact with foundations, and so forth—plus some visions for its future development.